Mitochondrial quality control mediated by PINK1 and PRKN: links to iron metabolism and tumor immunity. Issue 1 (2nd January 2019) - Kang, Rui; Xie, Yangchun; Zeh, Herbert J.; Klionsky, Daniel J.; Tang, Daolin
ABSTRACT: Mitochondrial quality control is an essential process required to maintain cellular homeostasis and functions. Mutations of PINK1 and PRKN/PARK2 contribute to the risk of Parkinson disease. Our recent findings indicate that depletion of Pink1 and Prkn promotes pancreatic tumorigenesis in KRAS-driven engineered mouse models. Mechanistically, PINK1- and PRKN-mediated autophagic degradation of mitochondrial iron importers (e.g., SLC25A37 and SLC25A28) suppresses pancreatic tumor growth by attenuating mitochondrial iron accumulation, inflammasome activation, HMGB1 release, and subsequent immune checkpoint expression. Consequently, pharmacological or genetic inhibition of mitochondrial iron-dependent signals prolongs animal survival and reverses pancreatic tumor phenotype in vivo . Thus, PINK1- and PRKN-mediated immunometabolism provides new insights into the tumor microenvironment and could be a suitable target for new pancreatic cancer treatments.